P290 Therapeutic requirements in patients with Ulcerative Proctitis. Is it necessary immunosuppressive therapy in these patients?. (21st January 2022) - Ferreiro Iglesias, R; Porto Silva, M S; Marín, S; Casanova, M J; Mañosa, M; González-Muñoza, C; de Francisco, R; Caballol, B; Arias, L; Piqueras, M; Zabana, Y; Rivero, M; et al.
Abstract: Background: Ulcerative proctitis may have a mild and less aggressive course, although evidence is scarce because these patients are excluded from participation in randomized controlled clinical trials. The aim is to identify clinical characteristics and complications associated with ulcerative proctitis refractory to conventional therapy. Methods: Patients included in the prospectively maintained ENEIDA registry from GETECCU with ulcerative proctitis were included. Socio-demographic data were evaluated. We defined ulcerative proctitis based on ECCO guidelines and immunosuppression as the use of immunomodulators and/or biologics. Logistic regression was used to identify the independent factors associated with immunosuppressive therapy among the different socio-demographic data. Results: From a total of 34.716 patients with ulcerative colitis, 6281 (18%) patients with ulcerative proctitis were identified. Mean age was 53 ± 15 years and mean duration of illness was 12 ± 9 years. Surgery was necessary only in 2% of patients, 31 (0.5%) panprotocolectomy or subtotal colectomy. The clinical characteristics of the patients with and without immunosupressive therapy are summarized at table 1. A total of 3691 patients received oral 5-ASA (58.8%) and 4652 (74.1%) topic 5ASA. 636 (10.1%) were refractory to 5-ASA and corticosteroids, necessitating immunosuppression: 459 patients with azathioprine (7%), 28 with 6-mercaptopurine (0.4%), 49 with methothrexate (0.8%), 191 with infliximab (9%), 125 with adalimumab (2%), 50 with golimumab (0.8%), 57 with vedolizumab (0.9%), 6 with ustekinumab (0.1%) and 3 with tofacitinib (0.0). 316 (5%) patients needed one biologic therapy, 95 (1.5%) needed 2 biologics and 40 (0.6%) at least three different biologics. Longer duration of illness and use of corticosteroids were associated with higher risk of immunosuppression. Conclusion: Good clinical outcomes were recorded in ulcerative proctitis, with only 10% of patients treated with immunosuppression therapy. The risk factors of immunosuppression were longer duration of illness and use of corticosteroids.